A Biblical Hebrew lexicon for translators based on recent developments in theoretical lexicography - Imbayarwo, Taurai (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DLitt (Ancient Studies))--University of Stellenbsoch, 2008.